Self-Care Management, Hemodialysis Duration, and Mental Well-Being in Hemodialysis Patients - Hestiningrum, Woro Astuti; Febriana , Betie; Setyowati , Wahyu Endang (Health Access Journal, 2026)
Hemodialysis patients are at high risk of psychological disturbances that compromise their mental well-being, yet the contribution of self-care management and treatment duration to this outcome remains insufficiently described in Indonesian hospital settings. This study aimed to examine the correlation between self-care management and mental well-being, and between hemodialysis duration and mental well-being, among hemodialysis patients. A cross-sectional correlational design was used with a total sampling technique, involving 114 respondents from Sari Asih Karawaci and Sari Asih Sangiang Hospitals. Mental well-being was measured using the validated Psychological Well-Being Scale (PWBS), and self-care management was measured using the validated Hemodialysis Patients Self-Care Management Scale; hemodialysis duration was obtained from medical records. Data were analyzed using Somers’ Gamma test. Results showed a significant moderate correlation between self-care management and mental well-being (p = 0.000; R = 0.596) and between hemodialysis duration and mental well-being (p = 0.014; R = 0.419). These findings indicate that better self-care management and longer hemodialysis duration are associated with improved mental well-being. Nurses are recommended to strengthen self-care education for hemodialysis patients, and future research should explore additional psychosocial factors influencing mental well-being using longitudinal designs.